(untitled) (Journal of Economic Research & Business Administration, 2018)
The development of innovative activity is the main component of the competitiveness of any country. Insufficient degree of innovative development is observed not only in the industries for the goods production, but also in the service sector. This article, supporting the role of creating and introducing innovations in the market development of a particular industry, is designed to study the relationship between the parallel movement of these processes. The purpose and scientific ideas are to study the possibilities of increasing the innovative activity of enterprises in relation to the information technology market in the Republic of Kazakhstan. The methodology of the study was based on the study of the works of foreign and domestic authors using theoretical generalization, system and comparative analysis, the method of statistical data processing. The scientific and practical significance of the work consists in obtaining the research results: a model for the development of the IT market in relation to the innovative potential of the economy through the development of an integrated strategy is proposed; the basic tendencies of development of the IT market in the Republic of Kazakhstan for a number of years have been determined, which made it possible to reveal the trend of its movement; provides basic data on the development of innovative capacity and identifies the necessary tools for technological modernization in the country; the possibility of developing start-ups as an effective tool for developing innovative activity in the IT market of the Republic of Kazakhstan with an approximate scheme of their work; the necessity and possibilities for introducing high-tech products and innovations into the activity of enterprises, marketing cross-functional measures and a procedural algorithm for determining the subjects of the market of study are studied. Conclusions of the research confirm that the problem should be considered through the context of parallel development of the IT market and innovation activity in the country, which will ultimately lead to the synergy effect. Although this study is far from exhaustive, it represents a definite step in understanding the conditions under which the economy of the industry thrives.